Impact of multidimensional airflow and internal radiation heat exchange in thermally massive wall assemblies utilizing cold-formed steel framing and reflective insulation - Saber, Hamed H. (Frontiers in Mechanical Engineering, 2025)
Thermal bridging due to high-conductivity metal elements in steel-framed systems can affect building performance. The presence of thermal bridges, radiative heat exchange between air-facing surfaces, and natural convection driven by buoyancy effects within cavities contribute to complex 3D airflow and heat transfer phenomena within these systems. With the wide range of reflective and mass insulation properties used in steel-framed wall assemblies, this study employs a previously developed and validated 3D numerical model to evaluate the thermal performance of a reflective insulation system (RIS) and a hybrid system that integrates reflective insulation with conventional mass insulation. Additionally, a methodology aligned with ASTM C1224 is introduced for separating the thermal bridging effects of steel framing elements to allow for evaluating the thermal resistances of wall cavities in RIS and hybrid systems. This work demonstrates, for the first time to the author’s knowledge, the coupled effects of conduction, convection, radiation, and airflow in steel-framed assemblies incorporating reflective insulation with and without conventional mass insulation. It further identifies a previously unreported critical conductivity threshold where partial and full cavity insulation yield equivalent resistance and provides data to extend current standards that omit RIS. The findings indicate that for mass insulation materials with low thermal conductivity, wall systems in which cavities are completely filled with insulation exhibit greater thermal resistance than those with only partially filled cavities. However, as the thermal conductivity of the insulation increases, the trend reverses, with partially filled cavities providing higher thermal resistance than completely filled ones. There exists a critical thermal conductivity threshold at which the thermal resistance of both configurations becomes equivalent. Beyond this point, wall systems with less insulation in their cavities can achieve superior thermal resistance to those where the cavities are completely filled. Given that existing design guidelines, such as Thermal Design and Code Compliance for Cold-Formed Steel Walls, do not currently address RIS, the data generated in this study provide a foundation for future updates. By integrating RIS and hybrid systems into thermal design practices, this research supports the development of cost-effective, high-performance steel-framed wall systems that enhance energy efficiency while maintaining material and regulatory compliance.